The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/sla.0000000000001474
|View full text |Cite
|
Sign up to set email alerts
|

Cosmesis and Body Image in Patients Undergoing Single-port Versus Conventional Laparoscopic Cholecystectomy

Abstract: This is the first multicenter double-blinded RCT reporting superior short- and long-term cosmetic and body image, postoperative pain, and QoL in SPLC compared with 4PLC. Although cost-effectiveness is still a subject of ongoing debate, SPLC should be offered to patients undergoing surgery for benign gallbladder disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 32 publications
2
77
0
Order By: Relevance
“…However, the objective and reproducible evaluation of QOL is not easy, especially in minimally invasive surgery or simple basic surgical procedure. Recently, for cholecystectomy, double-blinded RCT evaluating QOL between singleport cholecystectomy and conventional laparoscopic cholecystectomy was firstly reported (10). Using previously validated cosmesis and body image scores, and short form 36 health survey questionnaire SF-36, this study reported the statistical advantage of cosmesis and body image, higher QOL regarding emotional wellbeing, physical pain, physical health and mental health after postoperative 1 year, and less postoperative pain in single port cholecystectomy (47)(48)(49).…”
Section: Outcome and Understandingmentioning
confidence: 83%
See 1 more Smart Citation
“…However, the objective and reproducible evaluation of QOL is not easy, especially in minimally invasive surgery or simple basic surgical procedure. Recently, for cholecystectomy, double-blinded RCT evaluating QOL between singleport cholecystectomy and conventional laparoscopic cholecystectomy was firstly reported (10). Using previously validated cosmesis and body image scores, and short form 36 health survey questionnaire SF-36, this study reported the statistical advantage of cosmesis and body image, higher QOL regarding emotional wellbeing, physical pain, physical health and mental health after postoperative 1 year, and less postoperative pain in single port cholecystectomy (47)(48)(49).…”
Section: Outcome and Understandingmentioning
confidence: 83%
“…In terms of general surgery including appendectomy or cholecystectomy, recent several studies have reported that SILS is feasible and has similar surgical outcome without increasing significant complication (7)(8)(9)(10). In terms of malignancy of digestive tract, SILS has been eagerly investigated in colorectal cancer and showed comparable outcome in a few studies including randomized clinical trial…”
Section: Introduction For Single-incision Laparoscopic Surgery (Sils)mentioning
confidence: 99%
“…In a recent randomised controlled trial comparing cholecystectomy and intra-operative cholangiogram with endoscopic duct assessment followed by cholecystectomy from the group in Geneva, quality of life was assessed as a secondary endpoint using EuroQol-5D scores [6]. And, quality of life was a secondary endpoint in another recent Swiss study evaluating cosmesis and body image after SILS versus conventional laparoscopic cholecystectomy [13]. …”
Section: Discussionmentioning
confidence: 99%
“…4 After the introduction of this new technique, more than a dozen randomized clinical trials were conducted to compare SILC with 4PLC. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] These trials were designed to focus on cosmesis, pain, or quality of life (QOL), with patient-reported outcomes to evaluate subjectively the degree of patient suffering. In particular, QOL is drawing attention as a key measure to understand how patients evaluate their physical, mental, or social health status.…”
Section: Introductionmentioning
confidence: 99%